2012
DOI: 10.1044/1092-4388(2011/10-0281)
|View full text |Cite
|
Sign up to set email alerts
|

The Processing and Interpretation of Verb Phrase Ellipsis Constructions by Children at Normal and Slowed Speech Rates

Abstract: Purpose To examine children’s comprehension of verb phrase (VP) ellipsis constructions in light of their automatic, online structural processing abilities and conscious, metalinguistic reflective skill. Method Forty-two children ages 5 through 12 years listened to VP ellipsis constructions involving the strict/sloppy ambiguity (e.g., “The janitor untangled himself from the rope and the fireman in the elementary school did too after the accident.”) in which the ellipsis phrase (“did too”) had 2 interpretation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 51 publications
(110 reference statements)
1
4
0
Order By: Relevance
“…However, in follow-up analyses examining the effect of age on priming for each meaning separately (using the same regression approach described above, except that only relatedness, age, and their interaction were included as fixed effects), the priming effects did not change reliably as a function of age for either meaning (i.e., the interaction between Age and Relatedness was non-significant: Literal p=0.28; Idiomatic p=0.41), suggesting that this is not actually the case. Thus the results appear consistent with prior results of on-line processing developing in advance of off-line ability [ 16 19 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, in follow-up analyses examining the effect of age on priming for each meaning separately (using the same regression approach described above, except that only relatedness, age, and their interaction were included as fixed effects), the priming effects did not change reliably as a function of age for either meaning (i.e., the interaction between Age and Relatedness was non-significant: Literal p=0.28; Idiomatic p=0.41), suggesting that this is not actually the case. Thus the results appear consistent with prior results of on-line processing developing in advance of off-line ability [ 16 19 ].…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, adult-like formation of dependency links in real time has been demonstrated with other complex sentence constructions as well. In one study, a group of 4–6 year old children showed adult-like on-line comprehension of relative clause structures; [ 18 ]; in another, a group of 5–12 year olds showed adult-like on-line comprehension of verb-phrase ellipsis constructions [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Though the issue as to the reconstruction mechanism is not yet settled, findings from studies on verb-phrase ellipsis and on sluicing, i.e. elision of an entire clause except for a wh-word (e.g., Humphrey ordered something but Spencer doesn't know what Humphrey ordered) converge in suggesting that the elided element is reconstructed in real time -immediately when or shortly after encountering the ellipsis (e.g., Callahan, Walenski, & Love, 2012;Poirier, Wolfinger, Spellman, & Shapiro, 2010;Shapiro & Hestvik, 1995;Shapiro, Hestvik, Lesan, & Garcis, 2003: Yoshida, Dickey, & Sturt, 2013.…”
Section: Introductionmentioning
confidence: 99%
“…The vertical 'both' EPS construction found in these data, ensures the cohesion of early dialogues. The linguistic constructions of dialogue have been widely studied (Berko-Gleason & Ratner, 2009), both as part of early pragmatic development (for a review, see Bryant, 2009) and as a determining variable in the process of early language acquisition (Veneziano, 2010). Our results make specific this relationship for the Spanish language.…”
Section: Discussionmentioning
confidence: 54%